(untitled) (Kathmandu University Medical Journal, 2014)
The central nervous system (CNS) was once considered to be an immune-privileged area. However, increasing evidence shows that the central nervous system is not an immune-privileged but is an active surveillance site. There is a bi-directional communication between the central nervous system and immune system. Normally, immune cells migrate into the central nervous system microenvironment through choroid plexus and interact with the central nervous system resident cells through either through neuromediators or immunomediators. This finding has led to a significant interest in neuroimmunological interactions and investigation onto the role of the immune system in the pathology of various neurological disorders and examine whether it can be targeted to produce novel therapeutic strategies. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11055 Kathmandu University Medical Journal Vol.11(1) 2013: 102-107